A Common Traditional Woman's Life Story - Gómez García, Heiner Fabián; Morales Parada, Erika Natalia (Universidad Pedagógica y Tecnológica de Colombia, 2021)
A story written by Heiner Gómez and Erika Morales that speaks about a young woman who wants to break away from tradition.